Serious adverse reaction associated with the COVID-19 vaccines of BNT162b2, Ad26.COV2.S, and mRNA-1273: Gaining insight through the VAERS - Yan, Ming-Ming; Zhao, Hui; Li, Zi-Ran; Chow, Jun-Wei; Zhang, Qian; Qi, Yu-Peng; Wu, Shu-Shan; Zhong, Ming-Kang; Qiu, Xiao-Yan (Frontiers in Pharmacology, 2022)
Background and purpose: Serious adverse events following immunization (AEFI) associated with the COVID-19 vaccines including BNT162b2 (Pfizer-BioNTech), Ad26.COV2.S (Janssen), and mRNA-1273 (Moderna) have not yet been fully investigated. This study was designed to evaluate the serious AEFI associated with these three vaccines. Methods: A disproportionality study was performed to analyze data acquired from the Vaccine Adverse Event Reporting System (VAERS) between January 1, 2010 and April 30, 2021. The reporting odds ratio (ROR) method was used to identify the association between the COVID-19 vaccines BNT162b2, Ad26.COV2.S, and mRNA-1273 and each adverse event reported. Moreover, the ratio of the ROR value to the 95% CI span was applied to improve the credibility of the ROR. The median values of time from vaccination to onset (TTO) for the three vaccines were analyzed. Results: Compared with BNT162b2 and mRNA-1273, Ad26.COV2.S vaccination was associated with a lower death frequency (P < 0.05). Ad26.COV2.S vaccination was associated with a lower birth defect and emergency room visit frequency when compared with BNT162b2 (P < 0.05). There were 6,605, 830, and 2,292 vaccine recipients that suffered from COVID-19-related symptoms after vaccination with BNT162b2, Ad26.COV2.S, and mRNA-1273, respectively, including people who were infected by COVID-19, demonstrated a positive SARS-CoV-2 test, and was asymptomatic. Serious AEFI, including thromboembolism, hemorrhage, thrombocytopenia, cardiac arrhythmia, hypertension, and hepatotoxicity were associated with all three vaccines. Cardiac failure and acute renal impairment events were associated with BNT162b2 and mRNA-1273, while seizure events were associated with BNT162b2 and Ad26.COV2.S. The median values of TTO associated with the three vaccinations were similar. Conclusion: These findings may be useful for health workers as well as the general public prior to inoculation, especially for patients with underlying diseases, however, the risk/benefit profile of these vaccines remain unchanged. The exact mechanism of SARS-CoV-2 vaccine-induced AEFI remains unknown, and further studies are required to explore these phenomena.